Determinação de índice de sustentabilidade com indicadores das dimensões ambiental, social, econômica e técnica no perímetro irrigado Poção da Ribeira em Sergipe - Pinto Júnior, Ezio dos Santos (2025)
Several studies have been conducted to develop sustainability indicators for water resources in social, economic, and environmental dimensions. However, no research was found that established a sustainability index for irrigated perimeters considering social, economic, environmental, and technical dimensions. Therefore, the objective of this thesis is to apply methodologies, models, and procedures for sustainability analysis to improve water and energy use efficiency, as well as the socioeconomic and environmental qualities of the Poção da Ribeira Irrigation Perimeter in the state of Sergipe, Brazil. The sustainability index of the irrigated perimeter will serve as a guide for decision-making regarding the management, operation, and maintenance of water and energy, enabling their rational use. It will also provide a comparative parameter for sustainability analysis in production systems. The hypothesis is that the higher the defined sustainability index, the better the water efficiency in the evaluated property, leading to greater productivity gains. The interdisciplinary aspect of this research lies in the need to assess not only economic and agronomic issues but also the acceptance of this irrigation planning model by local farmers. This includes understanding its viability while considering cultural and social factors affecting the farmer and their family. The Poção da Ribeira Irrigation Perimeter is located between the municipalities of Itabaiana and Areia Branca in Sergipe. It encompasses a total area of 1,970 hectares, of which 1,100 hectares are irrigable, but only 507 hectares are currently irrigated across 466 plots. The main crops grown in the region include lettuce, peanuts, sweet potatoes, green onions, cilantro, kale, beans, among others. The predominant irrigation system is conventional sprinkling, although localized and micro-sprinkler irrigation methods are also used. For the environmental indicator, the index of irrigated area occupation will be determined. The methodology for determining the sustainability index for the irrigation perimeter is based on the model described by Sobral (2012), which aims to qualify social, environmental, economic, and technical indices. The sustainability index was obtained by calculating the value of the area formed by the variables (indicators) when plotted on a radar-type graph, a methodology proposed by Calorio (1997) and adapted by Faccioli and Gomes (2021). The results revealed that the sustainability index of the Poção da Ribeira Irrigation Perimeter is low, making it unsustainable over time, as the obtained value was 17.61283 on a scale from 0 to 100. Specifically, values between 0 and 20 are considered unsustainable for the studied environment. Recommendations for improving the sustainability index in the Poção da Ribeira Irrigation Perimeter include: Conducting awareness campaigns, such as promoting biological control to reduce pesticide use. Long-term initiatives, such as training farmers on the application of appropriate water depths for specific crops to enable sustainable water use. Capacity-building to increase income by promoting crops with higher economic value suitable for the region. Training for soil sampling and analysis to ensure accurate fertilizer recommendations for rural properties.